Diaspora and Migration in International Business—An African Perspective by Professor Helena Barnard - Elo, Maria; Barnard, Helena (Journal of Comparative International Management, 2025)
<span style="color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This article contributes with the insights and reflections by Professor Helena Barnard, a distinguished scholar in the field of international business. Drawing on her extensive experience and knowledge, this interview provides a specifically African perspective on diaspora and migration in the context of international business and entrepreneurship. Professor Barnard’s research has illustrated various mechanisms and actors shaping international business, organizational practices, and global business landscapes. Her insights on diaspora and migration contribute to theorizing their role and impact and provide novel suggestions fostering scholarly research and critical discussions.